AKSELERATOR FILANTROPI SYARIAH: SIGNIFIKANSI ROA, ROE, DAN FDR DALAM MENENTUKAN BESARAN ZAKAT BANK MUAMALAT - Riries Restu Ningsih; Mufti Arief Arfiansyah (Jurnal Ilmiah Ekonomi Islam, 2026)
The purpose of this study isto determine whether financial performance, which includes Return On Assets (ROA), Return On Equity (ROE), and Financing to Deposit Ratio (FDR), has a significant effect on Bank Muamalat's zakat expenditure, both partially and simultaneously. This study applies aquantitative method The data sources and samples used consist of Bank Muamalat Indonesia's quarterly financial reports from 2015 to 2024, which are available in full. Data collection was carried out using the documentation method. The data used is secondary data obtained from the official website of BankMuamalat. To analyze the information obtained, this studyapplies the multiple linear regression method. The research findings indicatethat ROA and ROE do not have a significant effect onBank Muamalat's zakat expenditure, while FDR shows a significant effect. Overall, the three variables, namely ROA, ROE, and FDR, have a significant effecton zakat expenditure at Bank Muamalat.